Health‐related quality of life and health status in persons with haemophilia A with inhibitors: A prospective, multicentre, non‐interventional study (NIS). Issue 3 (24th April 2019) - Mahlangu, Johnny; Oldenburg, Johannes; Callaghan, Michael U.; Shima, Midori; Mancuso, Maria Elisa; Trask, Peter; Recht, Michael; Garcia, Claudia; Yang, Renchi; Lehle, Michaela; Macharia, Harrison; Asikanius, Elina; et al.
Abstract : Introduction: Real‐world data (RWD) on health‐related outcomes in persons with haemophilia A (PwHA) provide insights into patient needs and can guide clinical study design. A global, prospective, non‐interventional study (NIS; NCT02476942) collected detailed RWD on bleeding outcomes, health‐related quality of life (HRQoL) and health status in PwHA treated per local routine clinical practice. Aim: To report HRQoL and health status in the adult/adolescent PwHA with inhibitors cohort in the NIS. Methods: This cohort enrolled PwHA aged ≥12 years with high‐titre factor VIII inhibitor history. Participants remained on their usual treatment (no protocol‐specified interventions). Health‐related outcomes: Haemophilia Quality of Life Questionnaire for Adults (Haem‐A‐QoL), Haemophilia‐specific Quality of Life Questionnaire for Children Short Form (Haemo‐QoL SF), EuroQol 5‐Dimensions 5‐Levels (EQ‐5D‐5L) index utility score (IUS) and visual analogue scale (EQ‐VAS). Results: One hundred three participants were enrolled on episodic (n = 75) or prophylactic treatment (n = 28); median (range) age, 31 (12‐75) years; median (range) observation time, 26 (4‐70) weeks. Haem‐A‐QoL scores indicated impairments in HRQoL aspects; comparable between episodic/prophylactic regimens and relatively consistent over time. Haemo‐QoL SF scores with both regimens varied over time, and appeared poorer with episodic than prophylactic treatment. IUS and EQ‐VAS were comparable between regimens, stable over time and lower on bleeding days. Mean proportions of missed work and school days were 16% and 23%, respectively; mean (standard deviation) number of days hospitalized was 3.2 (8.8) (comparable between groups). Conclusions: These RWD demonstrate that PwHA with inhibitors have impaired HRQoL, despite standard treatment, and that more effective treatment options are needed.